A case of transverse vaginal septum causing obstructed labour - Bello, Saratu; Eze, Ukwu; Umar, Adoke (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Transverse vaginal septum (TVS) is a congenital mullerian malformation resulting from failure of fusion or canalization of the urogenital sinus and the mullerian ducts. This results in amenorrhea, inability to consummate marriage and primary infertility if left untreated. It is a rare finding in pregnancy and labor. However, due to ignorance, poor health seeking behavior and poverty in our setting the diagnosis of transverse vaginal septum may only be encountered in labor. We describe an 18 year old primigravida at term presented with history and findings of obstructed labor due to transverse vaginal septum (low-type) with a small central aperture first diagnosed in labor. This report is aimed at alerting clinicians that all primigravidae should have a routine pelvic examination during their antenatal visit to rule-out lower genital abnormalities.